Decrease of Mutual Information in Brain Electrical Activity of Patients with Relapsing-Remitting Multiple Sclerosis - Bruno Lenne; Jean-Luc Blanc; Jean-Louis Nandrino; Philippe Gallois; Patrick Hautecæur; Laurent Pezard (Behavioural Neurology)
The disturbance of cortical communication has been hypothesized as an important factor in the appearance of cognitive impairment in (MS). Cortical communication is quantified here in control subjects and patients with relapsing-remitting multiple sclerosis (RRMS) on the basis of mean coherence in the δ, θ, α, β and γ bands and using mutual information computed between pairs of bipolar EEG signals recorded during resting condition. Each patient received also a cognitive assessment using a battery of neuropsychological tests specific to cognitive deficits in MS.